2002
DOI: 10.1155/2002/517163
|View full text |Cite
|
Sign up to set email alerts
|

A Short Version of the Pain Anxiety Symptoms Scale (PASS‐20): Preliminary Development and Validity

Abstract: BACKGROUND:Research has shown significant relations between fear and avoidance of pain and the suffering and disability of chronic pain. Effective measurement tools have formed the foundation for studying these relations. METHODS: The present article describes the initial development and validation of the PASS-20, a short form version of the Pain Anxiety Symptoms Scale (PASS). Like the original inventory, the PASS-20 measures fear and anxiety responses specific to pain. Items were selected for the short versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
447
4
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(473 citation statements)
references
References 21 publications
18
447
4
4
Order By: Relevance
“…A 20-item revised version of the PASS was used in the present study [13]. The PASS contains four subscales that measure the levels of various types of anxiety: cognitive anxiety, fear of pain, escape and avoidance, and physiologic anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…A 20-item revised version of the PASS was used in the present study [13]. The PASS contains four subscales that measure the levels of various types of anxiety: cognitive anxiety, fear of pain, escape and avoidance, and physiologic anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been used extensively in research and clinical practice and has been shown to be valid and reliable. 23 Pain Anxiety Symptoms Scale-20 (PASS-20): The PASS-20 56 is a shortened 20-item version of the original Pain Anxiety Symptoms Scale 25 designed to measure fear and anxiety responses specific to pain, including avoidance. The PASS-20 has four five-item subscales, including (1) cognitive anxiety, (2) escape and avoidance, (3) fearful thinking, and (4) physiological anxiety.…”
Section: Pain and Anxiety Questionnairesmentioning
confidence: 99%
“…The PASS-20 has been shown to have good to excellent reliability and validity. 56 APPENDIX B -Richmond Agitation-Sedation Scale Patient demonstrates eye opening and eye contact that is sustained for more than 10 seconds (score -1).…”
Section: Pain and Anxiety Questionnairesmentioning
confidence: 99%
“…Several psychological variables are also evaluated: (1) the Pain Catastrophizing Scale (PCS), a 13-item questionnaire which evaluates pain-related rumination, helplessness and magnification [39]; (2) Spielberger's State-Trait Anxiety Inventory (STAI), which allows a distinction to be made between anxiety as a trait of personality or an emotional response to a situation [40]; (3) the Beck Depression Inventory (BDI-II), a 21-item questionnaire assessing symptoms of depression [41]; (4) the Pain Anxiety Symptoms Scale (PASS-20), evaluating fear of pain during intercourse [42]; and (5) the Patient's Global Impression of Change (PGIC), a patient-reported measure selected to evaluate perceived reduction in pain using a 7-point scale that ranges from 'very much improved' to 'very much worse' [43].…”
Section: Primary Outcome Measurementioning
confidence: 99%